PENGARUH PROFITABILITAS, OPERATING LEVERAGE, TERHADAP NILAI PERUSAHAAN, DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rexyan Puspita Ningrum; Sri Hermuningsih (FE Program Studi Manajemen, 2019)
The objectives study are (1) to find and examine the effect of profitability on corporate value on Food and Beverage companies listed on the Indonesia Stock Exchange for the period 2013-2017, (2) to find and examine the effect of Operating Leverage on Company Values ​​on registered Food and Beverage companies on the Indonesia Stock Exchange for the period 2013-2017, (3) To find and examine the effect of Capital Structure on Company Values ​​on Food and Beverage companies listed on the Stock Exchange for the period 2013-2017, (4) To find and examine the effect of Profitability on Capital Structure in Food and Beverage listed on the Indonesia Stock Exchange for the period 2013-2017, (5) To find and examine the effect of Operating Leverage on Capital Structure in Food and Beverage companies listed on the Stock Exchange for the period 2013-2017. The research sample was 12 companies using the Purposive Sampling method. Analysis of the data used is the analysis of Multiple Regression and Path Analysis. The results of this study are (1) Profitability (ROA) has a negative and significant effect on Capital Structure (DER). (2) Operating Leverage (DOL) has a negative and significant effect on Capital Structure (DER). (3) Profitability (ROA) has a positive and significant effect on Company Value (PBV). (4) Operating Leverage (DOL) affects the Company Value (PBV). (5) Profitability (ROA) affects the Company Value (PBV). Keywords: Profitability, Operating Leverage, Company Value, Capital Structure